Enhancing Green Productivity in Rural Communities: Empowering Local Economy through Innovative Red Guava Derivative Products - Indah Apriliana Sari Wulandari; Ida Agustini Saidi; Niko Fediyanto (Universitas Muhammadiyah Sidoarjo, 2023)
This scientific article presents a community engagement initiative aimed at improving the local economy and promoting sustainable practices in the rural village of Kebaron, Indonesia. The study focuses on harnessing the potential of the abundant red guava fruit through the application of Green Productivity (GP) principles. The research team conducted a series of activities, including problem identification, potential product analysis, training sessions on red guava derivative production, and environmental education. The results demonstrated the successful development of innovative red guava derivative products such as red guava ice cream, leather, and juice. By involving the community and promoting environmentally friendly production techniques, the project contributed to the establishment of a sustainable and eco-conscious local industry. The findings highlight the importance of integrating GP concepts into rural communities, providing valuable insights for global researchers and professionals in the field of sustainable production and community empowerment. Highlight: Unleashing the potential: The abundant harvest of red guava in the village of Kebaron presents an opportunity to optimize its benefits for the local community by implementing the concept of Green Productivity (GP). Innovative product derivatives: Through community involvement and education, the project focuses on creating innovative red guava derivative products such as ice cream, leather, and juice, showcasing the application of sustainable production practices. Online promotion for wider reach: Leveraging the power of online media, the project emphasizes the effective promotion and sales of the red guava derivative products, tapping into a larger consumer base and highlighting the importance of environmentally conscious production practices. Keyword: Green Productivity, Red Guava, Community Engagement, Sustainable Production, Rural Economy